The profile of patients with neoplastic wounds and nursing care: A cross-sectional study - Soares, Raquel de Souza; Cunha, Daianny Arrais de Oliveira da; de Oliveira, Aretha Pereira; Fuly , Patricia dos Santos Claro (Seven Editora, 2023)
Objectives: to identify the clinical characteristics of patients with neoplastic wounds admitted to the palliative care unit and discuss nursing care applied to this patient. Methods This is a cross-sectional, prospective and descriptive with quantitative approach. Data collection was performed at the palliative care of the National Cancer Institute (INCA IV), located in Rio de Janeiro January-RJ. Results: for the analysis of the characteristics a sample of 35 was evaluated patients who were hospitalized in the ward at the time of the research. In relation to the gender variable did not present statistically significant difference in males and female, as for the age variable, there was a clientele over 60 years of age, with low performance status (impaired functional capacity), very advanced, especially in patients with female breast carcinomas and Head and Neck Carcinomas in males. In the evaluation of the wound, it is observed the importance of knowing the clientele in order to follow the care planning. From the profile found, advanced staging is a complicating factor because the more profoundly increased the risk of bleeding and impairment of nerve endings, which demands conducts to control pain and hemorrhage. And as for the odor, it’s It is important to note that this symptom is one of the most bothersome for patients and. Therefore, to minimize it is important an effective control of the local microbiota, the proper management of cleaning solutions, coatings and environmental aromatizers. DOI:https://doi.org/10.56238/globalhealthprespesc-076